Comparison of the effectiveness of cognitive behavioral therapy-based nutrition counseling and standard nutrition counseling on meal remains and blood sugar levels in hospitalized diabetes mellitus patients - Emira Tri Silawati; Catur Saptaning Wilujeng (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
High levels of food waste among hospitalized patients, particularly those with type 2 diabetes mellitus (T2DM), may indicate a mismatch between hospital food services and patient acceptance, potentially affecting their glycemic control. This study aimed to evaluate the effectiveness of cognitive behavioral therapy (CBT)-based nutrition counseling in reducing food waste and blood glucose levels compared with standard nutrition counseling. A quasi-experimental study with a pretest–posttest control group design was conducted at Klaten Islamic General Hospital in March 2026. Forty-five patients with T2DM were assigned to three groups: CBT-based counseling, standard counseling, and control. Food waste was assessed using the Comstock method, and blood glucose levels were measured using a GlucoDR glucometer. Data were analyzed using the Wilcoxon, paired-samples t-, Kruskal–Wallis, and one-way ANOVA tests. Results: Significant differences were observed among the groups after the intervention. The CBT group showed the greatest reduction in food waste and blood glucose levels compared to the standard counseling and control groups (p = 0.001 and p < 0.001, respectively). In conclusion, CBT-based nutrition counseling was more effective than standard nutrition counseling and usual care in reducing food waste and improving glycemic control in patients with T2DM.